An Empirical Analysis of Initial Public Offerings Underpricing in Chinese Stock Market - WU, Yuchen (2015)
This dissertation provides an empirical investigation on the underpricing of initial public offerings (IPOs) in Chinese stock market and analyse the possible determinants which results in the underpricing. A sample of 1048 underpriced Chinese A-share IPOs data during the period from 2006 to 2014 are selected to test various hypotheses based on the previous theories and Chinese specific characteristics. Additionally, this dissertation also attempts to seek the effects of IPO reforms during 2009 to 2013.